Perlindungan Hukum Bagi Perusahaan Leasing Terhadap Debitur Wanprestasi - Ni Luh Ayu Regita Cahyani; I Nyoman Putu Budlarta; Ni Made Puspasutari Ujianti (Warmadewa Press, 2021)
Disputes often occur in leasing companies, one of them is breach of content. This activity is carried out by the debtor who should have an obligation to carry out achievements in a contract against the leasing company. The purpose of this research is to reveal the form of legal protection for leasing companies and the legal consequences that arise when the debtor makes an interpretation. This research uses normative legal research, which is studied using literature research. Sources of legal materials used are primary legal materials and tertiary legal materials which can support secondary legal materials. The materials that have been obtained are then analyzed using descriptive techniques, where this technique describes legal issues which are then interpreted systematically and grammatically. The results of the research reveal that the standard agreement provided by the leasing party contains rights and obligations that are borne by the debtor and if the obligations cannot be fulfilled, then a subpoena can be given to the debtor if the obligations are not fulfilled, the capital goods that become the object can be withdrawn, as a result. the debtor can lose the rights to the item and the leasing party can terminate the agreement unilaterally.